2016
DOI: 10.1101/091728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of obesity-linkedFTOrs9939609 variant on physical activity and dietary patterns in physically active men and women

Abstract: Running title: FTO and obesity riskWord count: 2,621 Disclosure: The authors declared no conflict of interest Abstract Objective: To examine physical activity and dietary patterns in physically active individuals carrying different risk variants of the fat mass and obesity-associated gene (FTO) rs9939609 single nucleotide polymorphism (SNP).Methods: A total of 528 white men and women (mean (SD): 34.9(9.5) years, 26.6(4.3) kg·m -2 ) were genotyped for FTO rs9939609 SNP. Sex, age and anthropometric measurements … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The genomic inflation coefficient (lambda) for the obesity 336 cohort was computed as 1.05. We also include eight SNPs found slightly above the significance 337 threshold in the FTO gene that are reported in several studies as obesity-related (Ehrlich and 338 Friedenberg 2016;West et al 2018). In comparison to the two quantitative-trait BMI GWASs, this 339 study identified several more associations around the NEGR1 gene on chromosome 1.…”
Section: Case-control Gwas Of Extreme Obesity In the Healthy Nevada Cmentioning
confidence: 97%
“…The genomic inflation coefficient (lambda) for the obesity 336 cohort was computed as 1.05. We also include eight SNPs found slightly above the significance 337 threshold in the FTO gene that are reported in several studies as obesity-related (Ehrlich and 338 Friedenberg 2016;West et al 2018). In comparison to the two quantitative-trait BMI GWASs, this 339 study identified several more associations around the NEGR1 gene on chromosome 1.…”
Section: Case-control Gwas Of Extreme Obesity In the Healthy Nevada Cmentioning
confidence: 97%